Strategi Optimalisasi Spray Dryer pada Pembuatan Kopi Instan dengan Response Surface Methodology - Khairol Mizan Us; Mawardi, Indra; Hanif (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Instant coffee is one of the products produced from the drying process using a spray dryer. The quality of instant coffee is usually influenced by many variables, especially the drying temperature. This study aims to evaluate the effect of the upper and lower temperatures of the spray dryer on three product quality parameters, namely yield, moisture content, and solubility, using the Response Surface Methodology (RSM) approach. Determination of optimal operating conditions needs to be done through a multi-response approach to obtain the best balance between high yield, low moisture content, and maximum solubility. The research method used the Box-Behnken Design (BBD) with 15 experimental runs. The variables varied were the upper temperature (150-220 °C), the lower temperature (50-100 °C), and the concentration of maltodextrin (0-30%). The observed responses included yield, moisture content, and solubility. The modelling results showed that the combination of upper and lower temperatures had a significant effect on product quality. The optimum conditions were obtained at an upper temperature of 164.496°C, a lower temperature of 100°C, and a maltodextrin concentration of 30%, with a yield of 91.214%, a moisture content of 0.698%, a solubility of 89.665%, and a desirability value of 0.711.